Acidotic depression of cyclic AMP accumulation and phosphorylase b to a transformation in skeletal muscle of man. - Chasiotis, D (1983)
Intravenous infusion of adrenaline was performed in three healthy subjects on two occasions. In one case subjects performed a maximal isometric contraction before infusion. Biopsies were taken from the quadriceps femoris muscle before and after infusion for 0.5 and 2 min, and analysed for muscle pH, cyclic AMP, metabolites and activities of glycogen phosphorylase and synthetase. Isometric contraction resulted in a decrease of muscle pH to 6.60 (normal value at rest 7.0-7.1). By this experimental procedure the effect of adrenaline infusion could be studied on a muscle with normal pH and one with low pH. Cyclic AMP increased from 3 to about 9.5 mumol per kg dry weight after 0.5 min of adrenaline infusion. When isometric contraction preceded the infusion, cyclic AMP increased more slowly and was about 5.5 mumol per kg dry weight after the same time of infusion. Phosphorylase a constituted about 22% of total phosphorylase in resting muscle but increased rapidly to 80% after 0.5 min infusion. When exercise preceded infusion phosphorylase a decreased and was still lower after 2 min infusion. The results can be explained by inhibition of adenylcyclase and phosphorylase b kinase at low muscle pH.